Comparison between Two-Layer Density Gradient and Three-Layer Density Gradient Technique for Sperm Preparation at Aster Fertility Clinic, Dr. Hasan Sadikin General Hospital - Nanang Winarto Astarto; Dian Tjahyadi; Sintya Jatnikasari (Faculty of Medicine Universitas Padjadjaran, 2014)
Objective: To compare the efficacy of sperm preparation techniques modified by two layer density gradient technique (80%, 40%). Methods: Sperm preparation was performed by two- and three-layer density gradient technique by centrifugation at 500 rpm for 20 minutes using SpermGrad (Vitrolife, Sweden). Results: The average concentration of total sperm preparation by two-layer density gradient was 23.19 million with a standard deviation of 11.9 million while the result of three-layer density gradient preparation obtained a mean total sperm concentration of 19.64 million with a standard deviation of 10.033 million. The mean total concentration of sperm in three-layer was lower than two-layer density gradient with p <0.001.Conclusions: This study concludes that there was a significant difference between the concentration of sperm prepared using two-layer and three-layers density gradient technique.Keywords: Density gradient, spermatozoa DOI: 10.15850/ijihs.v2n1.286